If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6(x + -4) = 4(3 + -2x) + 4 Reorder the terms: 4x + -6(-4 + x) = 4(3 + -2x) + 4 4x + (-4 * -6 + x * -6) = 4(3 + -2x) + 4 4x + (24 + -6x) = 4(3 + -2x) + 4 Reorder the terms: 24 + 4x + -6x = 4(3 + -2x) + 4 Combine like terms: 4x + -6x = -2x 24 + -2x = 4(3 + -2x) + 4 24 + -2x = (3 * 4 + -2x * 4) + 4 24 + -2x = (12 + -8x) + 4 Reorder the terms: 24 + -2x = 12 + 4 + -8x Combine like terms: 12 + 4 = 16 24 + -2x = 16 + -8x Solving 24 + -2x = 16 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 24 + -2x + 8x = 16 + -8x + 8x Combine like terms: -2x + 8x = 6x 24 + 6x = 16 + -8x + 8x Combine like terms: -8x + 8x = 0 24 + 6x = 16 + 0 24 + 6x = 16 Add '-24' to each side of the equation. 24 + -24 + 6x = 16 + -24 Combine like terms: 24 + -24 = 0 0 + 6x = 16 + -24 6x = 16 + -24 Combine like terms: 16 + -24 = -8 6x = -8 Divide each side by '6'. x = -1.333333333 Simplifying x = -1.333333333
| (x+21)+102=180 | | -24=-10+3 | | (3x-5)+2x=85 | | 2(3x-5)+x=85 | | -6x+39=-4x+25 | | -13x-5=-x-101 | | 3x-21+40=-5 | | 42*x=15.12 | | 4x+18=x+60 | | 5x-12=-2x+44 | | 6x-4=-4x-2 | | x*5=9.5 | | x-13=-7x+27 | | y=3.8 | | 7.3*x+2.7*x=10 | | (x+21)+102=108 | | 12x-20=x+24 | | 3x+2=4(x-1) | | o=4 | | 3(x-7)+40=-5 | | 5w+2n=12 | | 3-3x+1=16 | | 16=8/d | | -4x+2x=-6 | | 4(r+2)-r=3(r+1) | | (5*x*y^2-x^3)dx+(5*x^2*y-y)dy=0 | | 26=-7+6x-12-x | | 4.3*x=3.8*4.3 | | 3-4x-1=14 | | 8.7*x=8.7 | | 3(2d-9)+5d=17 | | -21u+3=-60u-8 |